2020
DOI: 10.51791/njap.v47i4.105
|View full text |Cite
|
Sign up to set email alerts
|

Lactating performance of West African dwarf does fed dietary levels of boiled rubber seed meal based diets

Abstract: Animal milk has been an outstanding balanced food for man, and a very good source of protein to man. The bulk of milk consumed in Nigeria is imported. An experiment was conducted with twelve lactating West African dwarf does that were at their second parity using graded levels (0%, 10%, 20% and 30%) of boiled rubber seed meal to investigate their colostrum and normal milk yield and proximate compositions. The rubber seeds were boiled for 30 minutes, dehulled and dried for three days before being milled and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Milk yield was not affected, but milk fat and total solid contents were reduced in dairy cows fed YERSEK in concentrate. In contrast, Udo et al [ 44 ] reported that milk yield and milk composition were unaffected by the inclusion of boiled rubber seed kernel at 10–30% in the concentrate of West African Dwarf goats. The unsaturated fatty acid content of the rubber seed kernel was 80.8%, mainly including 37.8% linoleic acid (C18:2) and 17.6% linolenic acid (C18:3) [ 7 ].…”
Section: Discussionmentioning
confidence: 98%
“…Milk yield was not affected, but milk fat and total solid contents were reduced in dairy cows fed YERSEK in concentrate. In contrast, Udo et al [ 44 ] reported that milk yield and milk composition were unaffected by the inclusion of boiled rubber seed kernel at 10–30% in the concentrate of West African Dwarf goats. The unsaturated fatty acid content of the rubber seed kernel was 80.8%, mainly including 37.8% linoleic acid (C18:2) and 17.6% linolenic acid (C18:3) [ 7 ].…”
Section: Discussionmentioning
confidence: 98%